Continuidade de atratores para problemas parabólicos semilineares sob perturbações do domínio - Samprogna, Rodrigo Antonio (Universidade Federal de São Carlos, 2013)
In this work we will obtain the continuity of attractors for semilinear parabolic problems with Neumann boundary conditions relatively to perturbations of the domain. We will show that, if the perturbations on the domain are such that the convergence of eingenvalues and eingenfunctions of the Neumann Laplacian is granted then we obtain the upper semicontinuity of the attractors. If, moreover, every equilibrium of the unperturbed problem is hyperbolic we also obtain the continuity of attractors
Keywords: Equações diferenciais parciais; Continuidade de atratores; Operador laplaciano; Pertubação (Matemática); CIENCIAS EXATAS E DA TERRA::MATEMATICA